Ecophysiological Plasticity and Bacteriome Shift in the Seagrass Halophila stipulacea along a Depth Gradient in the Northern Red Sea - Rotini, Alice; Mejia, Astrid Y.; Costa, Rodrigo; Migliore, Luciana; Winters, Gidon (Frontiers in Plant Science, 2017)
Halophila stipulacea is a small tropical seagrass species. It is the dominant seagrass species in the Gulf of Aqaba (GoA; northern Red Sea), where it grows in both shallow and deep environments (1-50 m depth). Native to the Red Sea, Persian Gulf, and Indian Ocean, this species has invaded the Mediterranean and has recently established itself in the Caribbean Sea. Due to its invasive nature, there is growing interest to understand this species' capacity to adapt to new conditions, which might be attributed to its ability to thrive in a broad range of ecological niches. In this study, a multidisciplinary approach was used to depict variations in morphology, biochemistry (pigment and phenol content) and epiphytic bacterial communities along a depth gradient (4-28 m) in the GoA. Along this gradient, H. stipulacea increased leaf area and pigment contents (Chlorophyll a and b, total Carotenoids), while total phenol contents were mostly uniform. H. stipulacea displayed a well conserved core bacteriome, as assessed by 454-pyrosequencing of 16S rRNA gene reads amplified from metagenomic DNA. The core bacteriome aboveground (leaves) and belowground (roots and rhizomes), was composed of more than 100 Operational Taxonomic Units (OTUs) representing 63% and 52% of the total community in each plant compartment, respectively, with a high incidence of the classes Alphaproteobacteria, Gammaproteobacteria and Deltaproteobacteria across all depths. Above and belowground communities were different and showed higher within-depth variability at the intermediate depths (9 and 18 m) than at the edges. Plants parts showed a clear influence in shaping the communities while depth showed a greater influence on the belowground communities. Overall, results highlighted a different ecological status of the H. stipulacea at the edges of the gradient (4-28 m), where plants showed not only marked differences in morphology and biochemistry, but also the most distinct associated bacterial consortium. We demonstrated the pivotal role of morphology, biochemistry (pigment and phenol content) and epiphytic bacterial communities in helping plants to cope with environmental and ecological variations. The plant/holobiont capability to persist and adapt to environmental changes likely has a pivotal role in its ecological resilience and invasiveness.